Socio-economic Effects of Covid-19 Pandemic on Rural Farm Families’ Well-Being and Food Systems in Imo State, Nigeria - Chikaire, J.U.; Ajaero, J.O.; Atoma, C.N. (Journal of Sustainability and Environmental Management, 2022)
This work ascertained the socioeconomic effects of covid-19 pandemic on rural farm families’ well-being and food systems in Imo State, Nigeria. The specific objectives were to examine farm families’ awareness of Covid-19 pandemic; identify information sources on Covid-19 pandemic, and determine the perceived effects on farm families’ well-being and food systems. Data were collected using well-structured questionnaire and complemented by oral interview. Purposive random sampling was used to select 452 respondents from farming communities in Imo State, Nigeria. The descriptive statistics including percentages, mean and standard deviation were used to further analyze the data. The results obtained revealed that the respondents were fully aware of covid-19 pandemic as shown by the use of face masks (100%), lock down (97.37%) imposition by the government, vaccination (99.5%), among others. Several sources of information exist on Covid-19 pandemic, such as radio (100%), television (75.5%), churches (88.4%), and town criers (99.5%). The effects on well-being and food systems includes loss of income (M=3.41), loss of employment (M=3.68), disruption of food supply (M=3.67), increased food cost (M=3.70), reduced food availability (M=2.89), death/illness (M=2.67), reduced food distribution (M=2.75) increased transport cost (M=3.41), increase food prices (M=2.91) among many others. DOI: https://doi.org/10.5281/zenodo.6206234